Understanding the demand side and coordinating the supply side for connected goods and services - Ladegård , Gro; Romstad, Eirik (Applied Studies in Agribusiness and Commerce, 2010)
This paper addresses the coordination and innovation issues needed for promoting value added at the rural and regional level. There are two sides to value added: the ability to meet consumer demand, and to identify least cost ways of supplying the demanded goods. Human and social capital plays an important role on both sides. At the municipality level the supply side issues are complex. First, because the production space has far more dimensions than for the single entrepreneur. Second, because the value of some goods and services produced depend on what other goods and services that is available. On the supply side networks are important to solve the coordination issues, while networks for identifying and understanding consumer preferences are important on the demand side. Participation in these two network types compete for the same scarce resource, the time of the inhabitants of a municipality. We address these issues in more detail. A major insight from our work is that in addition to the time conflict, innovation and new information may make it more difficult to maintain coordination networks.